Comparison of biomass and lipid production under ambient carbon dioxide vigorous aeration and 3% carbon dioxide condition among the lead candidate Chlorella strains screened by various photobioreactor scales. (December 2015) - Kobayashi, Naoko; Barnes, Austin; Jensen, Travis; Noel, Eric; Andlay, Gunjan; Rosenberg, Julian N.; Betenbaugh, Michael J.; Guarnieri, Michael T.; Oyler, George A.
Highlights: Chlorella species were classified by rDNA-based phylogenetic analysis. Selected Chlorella species were screened based on biomass and lipid production. The candidate strains were compared under vigorous aeration with air and 3% CO2 . Chlorella species of UTEX 395, 259 and 1230 yielded the most biomass and lipids. Depending on the carbon source the strains may be suited for biofuel applications. Abstract: Chlorella species from the UTEX collection, classified by rDNA-based phylogenetic analysis, were screened based on biomass and lipid production in different scales and modes of culture. The lead candidate strains of C. sorokiniana UTEX 1230 and C. vulgaris UTEX 395 and 259 were compared between conditions of vigorous aeration with filtered atmospheric air and 3% CO2 shake-flask cultivation. The biomass of UTEX 1230 produced 2 times higher at 652 mg L −1 dry weight under both ambient CO2 vigorous aeration and 3% CO2 conditions, while UTEX 395 and 259 under 3% CO2 increased to 3 times higher at 863 mg L −1 dry weight than ambient CO2 vigorous aeration. The triacylglycerol contents of UTEX 395 and 259 increased more than 30 times to 30% dry weight with 3% CO2, indicating that additional CO2 is essential for both biomass and lipid accumulation in UTEX 395 and 259.